Economic and ecological comparison of organic and non-organic farming: a case of green economy in Nepal. (2015) - Aryal, Pabitra; Bhuju, Dinesh Raj; Thapa-Parajuli, Resham Bahadur; Meiners, Scott J.
Farmers in Kathmandu Valley and its periphery traditionally practised organic farming but switched to non-organic after the advent of chemical fertilisers in search of better production. This study was an attempt to assess economic and environmental differences between organic and non-organic farming practices using a case study from Bhaktapur, a city near Kathmandu, Nepal. Methodology included economic comparisons, assessment of soil chemical parameters and weed biodiversity. It also explored market demand for organic product and consumer's willingness to pay. The survey showed that the average financial benefit from organic vegetable products was less than from non-organic farming while organic farming was more beneficial in environmental value. Furthermore, market demand for organic products was moderate while that of non-organic products was higher (seller's perception). Consumer is willing to pay a premium for organic products. Finally, the study found the environmental and social pillars were comparatively stronger than the economic in GE perspective.